112k views
2 votes
Simplify $\frac{2\sqrt[3]9}{1 + \sqrt[3]3 + \sqrt[3]9}.$

User Jaisa Ram
by
5.7k points

1 Answer

0 votes

Let
x=\sqrt[3]{3} and
x^2=\sqrt[3]{9}. Then


\frac{2\sqrt[3]{9}}{1+\sqrt[3]{3}+\sqrt[3]{9}}=(2x^2)/(1+x+x^2)

Multiply the numerator and denominator by
1-x. The motivation for this is the rule for factoring a difference of cubes:


a^3-b^3=(a-b)(a^2+ab+b^2)

Doing so gives


(2x^2(1-x))/((1+x+x^2)(1-x))=(2x^2(1-x))/(1-x^3)

so that


\frac{2\sqrt[3]{9}}{1+\sqrt[3]{3}+\sqrt[3]{9}}=\frac{2\sqrt[3]{9}(1-\sqrt[3]{3})}{1-3}=\sqrt[3]{9}(\sqrt[3]{3}-1)=3-\sqrt[3]{9}

User Miller Zhu
by
5.9k points